Predictive multiscale modeling for Unidirectional Carbon Fiber Reinforced Polymers. (20th January 2020) - Gao, Jiaying; Shakoor, Modesar; Domel, Gino; Merzkirch, Matthias; Zhou, Guowei; Zeng, Danielle; Su, Xuming; Liu, Wing Kam
Abstract: This paper presents a predictive multiscale modeling scheme for Unidirectional (UD) Carbon Fiber Reinforced Polymers (CFRP). A bottom-up modeling procedure is discussed for predicting the performance of UD structures. UD material responses are computed from high fidelity Representative Volume Elements (RVEs). A data-driven Reduced Order Modeling approach compresses RVEs into Reduced Order Models so material responses can be computed in a concurrent fashion along with the structural level simulation. The approach presented in this paper is validated against experimental data and is believed to provide design guidance for future fiber reinforced polymers development.